Between the Universal Church and the Local Church: Revisiting the Representative Function of Bishops in the Context of Communio Ecclesiology - Okpaleke, Ikenna Paschal (2022)
This article examines the ecclesiological tension caused by the nature of the Church as a singular and plural entity. As a singular entity, the Church is universal or catholic; in a plural designation, we speak of local or particular churches. The relationship between the universal and the local has generated many debates that have caused paradigm shifts within ecclesiology, from the hierarchical to the communio frameworks, and even synodality. In exploring these debates and their implications for some aspects of the legislative norms, as well as in the light of the contemporary conversations on synodality, the article address the theological question of the representative function of bishops. The evolution of the Synod of Bishops suggests that this long-running debate may be entering a new phase with the synodal processes that Pope Francis is promoting in the Church today.
Keywords: Pope Francis; Synodality; Communio ecclesiology; Bishops; local Church; Universal Church